“Viva o som!" A atualização das práticas de escuta em subgêneros do rock independente de Curitiba - Estivalet, Felipe Viana (Universidade do Vale do Rio dos Sinos, 2021)
With this thesis, I propose to understand how listening practices received in independent rock subgenres of the city of Curitiba were updated between the years 2016 and 2020. To face the research problem, I start from ethnographic approaches on and offline ( ANGROSINO, 2009; HINE, 2015a), unfolded in participant observation/ listening techniques, audiovisual consultations and semi-structured interviews with musicians, fans and producers of rock content independent from the capital of Paraná state. In the theoretical scope, the work is oriented through the dialogue between the so-called Communication Materialities (GUMBRECHT, 1994 and 2010; PEREIRA de SÁ, 2016) and the Sound Studies (PEREIRA de SÁ, 2010; STERNE, 2012; STEINTRAGER and CHOW, 2019), thought here as part of a “materialistic agenda” of the study of the intersections between communication, media, sound and music. In view of the proliferation of musical projects in specific indie subdivisions such as post genres (rock, hardcore, metal), shoegaze and dream pop in a context of consolidation of audio streaming platforms as the dominant form of music listening, the argument is that local listening practices (NOVAK, 2008) in independent rock of Curitiba, despite the permeability of digital media, unfold in complementary and articulated processes of 1) Self-taught audibility techniques generated in domestic contexts; 2) Production of private listening spaces in the urban environment; 3) Introspective sonic dominance in contexts of spatial and temporal co-presence of live presentations; 4) Micro-sociability of the circulation from the sound material. Such modes of listening, which are indications of a broader modern aural regime, would operate in a complementary way by updating listening practices historically constituted of such subdivisions of independent rock in a global context.
Keywords: Processos midiáticos; Materialidades da comunicação; Estudos de som; Práticas de escuta; Rock Independente; Mediatization; Materialities of communication; Sound studies; Practices of listening; Indie rock; ACCNPQ::Ciências Sociais Aplicadas::Comunicação